The need for supported education among higher education students with psychiatric disabilities - Goh, Siao Yen (2007)
The purpose of the research was to show the need for the empirically effective Supported Education among higher education students with psychiatric disabilities. Its main objective was to examine the relationships between elements of Supported Education existing in the lives of these students and their current performances (that is: academic achievement, self-esteem, school self-efficacy & illness symptoms). The second objective was to examine the relationships between the students’ coping difficulties and their current performances. The third objective was to survey the support for a Supported Education (SEd) program among these students. The research site was the state of Johor, Malaysia. The research was a survey by design, with a structured questionnaire as the instrument. Data from a sample of 30 respondents was collected and analysed using the SPSS version 13. Descriptive statistics showed an academic achievement (GPA) mean of 3.03, indicating academic capability; low level of coping difficulties faced by these students (who were currently studying and not taking an illness break); high level of SEd elements existing in their lives (the probable reason for their good current performance); high level of self-esteem (measured with the Rosenberg Self Esteem Scale), moderate level of school self-efficacy; and low level of illness symptoms/symptomatology. Inferential statistics showed significant relationships of moderate to very strong association between coping difficulties and their current performances. There were low insignificant relationships between SEd elements & selfesteem; and between SEd elements & school self-efficacy. A correlation between a subscale of SEd elements (academic support) and self-esteem revealed a moderate, close-tosignificant relationship. There was a negligible relationship with academic achievement while the relationship with illness symptom went in an unexpected direction. The low relationships with self-esteem and school self-efficacy implied the possibility of a stronger association if the elements of SEd inventory is improved in construct or more accurately investigated with a pre-test and post-test design on a trial SEd program. The moderate relationship with a sub-scale of SEd elements suggested that SEd improves the self-esteem. The negligible relationship with academic achievement may be consistent with literature while the Modified Colorado Symptom Index used to measure illness symptom may not be suitable after all for all three group disorders (mood, anxiety and psychotic). The strong associations between coping difficulties and current performances imply clearly that the coping difficulties of these students affect their performances. The students’ support for SEd was of a high level. In conclusion, higher education students with psychiatric disabilities do need and would benefit from a rehabilitation program such SEd. Recommendations based on the findings were made for policy makers, educators, mental health professionals & co-workers, NGOs, consumers and SEd researchers. Recommendations for future research were also made.